PARTISIPASI MASYARAKAT DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN DI KELURAHAN SEI PUTIH TENGAH KECAMATAN MEDAN PETISAH KOTA MEDAN - Putri, Aisyah Oktaviani (PERSPEKTIF, 2016)
This study aims to examine community participation in development planning participatory review of aspects of infrastructure or in the physical plane and the factors that hinder participation in participatory development planning. The study was conducted in the Village of White Sei Middle District of Medan Medan Petisah region known as the strategic and people's lives are pretty good. Forms of research is qualitative descriptive. Data collection techniques used in this research through interviews with related parties such as village officials, LPM, which is present in participatory development planning activities, and organizers of participatory development planning. In addition, another technique used is observation, and documentation. The data analysis technique used is descriptive analysis.The results showed that the level of public participation is being actif. Because to the active participation and passive participation made some communities in Middle Village White Sei when participation took place.